Complement 3d from molecular adjuvant to target of immune escape mechanisms - Bergmann-Leitner, Elke S (Clinical immunology (Orlando, Fla.), 2006)
C3d is a fragment of the complement factor C3 and is generated in the course of complement activation. When bound to antigen in single or multiple copies, the B cell receptor and complement receptor 2 become co-crosslinked resulting in decreased or increased B cell responses depending on the valence of the antigen-C3d construct. When antigen-C3d constructs are used for the purpose of generating a protective immune response (vaccines), they may either enhance the expected response or suppress it depending on the nature of the antigen. Various pathogens use C3d to evade the immune system by inhibiting complement activation, invading and homing in host cells or masking immunogenic areas of pathogen proteins. Therefore, future vaccination strategies for infectious diseases and cancer employing C3d as a molecular adjuvant need to be carefully evaluated before choosing a target antigen in order to take advantage of the adjuvant effect of the complement component while avoiding potential vaccine complications associated with immune escape mechanisms